THE IDEA AND THE STRATEGY OF TRANSNATIONAL SOCIAL MOVEMENT ABOUT RIGHT TO THE CITY IN INDONESIA - Aswin Baharuddin; Rial Ashari Bahtiar; Seniwati Ismail (Indonesia Social Justice Network (ISJN), 2019)
This article aims to explain the strategy of implementation of the Right to the City campaign by the organization of Kota Kita in Indonesia. Also, this study also aims to determine the opportunities and challenges of the Right to the City campaign in Indonesia. The research method used is a descriptive-analytic method. Data obtained through literature review and literature studies in the form of books, journals, documents, and various other sources. Data were analyzed qualitatively, while quantitative data were used as a support to clarify qualitative analysis. The results of this study indicate that there are several strategies implemented by Kota Kita in the implementation of the Right to the City campaign in Indonesia. The strategy involves utilizing transnational coalitions, campaigns through forums, campaigns through capacity building, working with governments and transnational organizations, as well as research and publications. Opportunities in Right to the City campaign by Kota Kita in Indonesia are public enthusiasm, the existence of the Global Platform for the Right to the City as a transnational coalition, and the government's cooperative role. Meanwhile, the challenge faced is that there is no legal basis for Right to the City explicitly.